A comparison of the performance of foreign & local initial public offerings - Fang, Jixian (2013)
Scholars have extensively examined the trends and motivations behind firms seeking to list in Singapore. However, little has been documented on the country specific factors and firm specific factors affecting the success of these listings in Singapore. This dissertation seeks to rigorously identify and analyse factors that affect the IPO performance of firms listed in Singapore. In-depth analyses would also be conducted on how these factors affect the performance of foreign firms as compared to local firms as well as the challenges foreign firms could face in maximising their proceeds from listing in Singapore.